2012
DOI: 10.3851/imp2315
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Prophylaxis for Breastfeeding Transmission in Malawi: Drug Concentrations, Virological Efficacy and Safety

Abstract: Maternal administration of these three regimens up to 6 months postpartum was effective and safe for both mothers and infants. No significant correlation was found between drug concentrations and infant haematological parameters, supporting the hypothesis that other factors may contribute to the development of anaemia in these settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 21 publications
5
44
0
3
Order By: Relevance
“…The remaining three studies 23,29,45 found that lamivudine BM : MP ratios were <1. The overall pooled estimate was 0.93 (95% CI 0.89–0.98).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The remaining three studies 23,29,45 found that lamivudine BM : MP ratios were <1. The overall pooled estimate was 0.93 (95% CI 0.89–0.98).…”
Section: Resultsmentioning
confidence: 97%
“…25 and Palombi et al . 23 performed longitudinal analyses on MP, BM and IP; given the half-life of 30 h for nevirapine in infants from a similar population, 26 by 3 months we presumed that detectable infant levels reflected BM transfer of drug. Both studies reported similar IP concentrations of ∼12% of MP at 14 weeks and <5% by 24 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lamivudine freely crosses the placenta and also is concentrated and excreted in breast milk [50][51][52][53][54][55]. Despite this, antiviral blood concentrations in breastfeeding neonates decrease over time, suggesting that lamivudine is either inefficiently absorbed by the newborn or that the total amount of lamivudine ingested from breast milk is negligible [56][57][58]. Tenofovir also crosses the placenta, but less freely than lamivudine.…”
Section: Breastfeedingmentioning
confidence: 91%